Strategi Pengembangan Kawasan Wisata Pantai Songka Di Kota Palopo - Muhammad Bibin; Ani Ardian (EDUTOURISM Journal Of Tourism Research, 2020)
Palopo City has coastal tourism potential that can be utilized. One of the coastal areas in Palopo City that has the potential to be a coastal tourist attraction is Songka Beach. But the problem in the Songka Beach Tourism Area is the lack of visitor interest on a typical day. This is due to the Songka Beach tourism area has not been developed optimally either by the community around the tourist attraction or the local government as well as the lack of tourism promotion. The facilities and infrastructure that can support the development of Songka Beach attractions are somewhat lacking. The purpose of this research is to design a strategy for developing Songka Beach tourism object so that it can benefit more optimally. The analysis used to determine the right strategy in developing Songka Beach is to use a process hierarchy analysis (AHP). Based on the results of research on ecological aspects which are the first priority in the development of Songka Beach tourism and strategies that are prioritized in the development of the Songka Beach Tourism Area are making the suitability map of Songka Beach tourism and calculating the carrying capacity of the tourist area with the aim that there are restrictions on the number of visitors who want to visit the area Songka Beach tourism so that the preservation of natural resources is maintained and not damaged.